2013
DOI: 10.3724/sp.j.1037.2011.00809
|View full text |Cite
|
Sign up to set email alerts
|

HETEROGENEOUS MICROSTRUCTURE AND TEXTURE EVOLUTION DURING FABRICATION OF Zr--Sn--Nb ZIRCONIUM ALLOY SHEETS

Abstract: Zirconium alloys are widely used as fuel cladding and structural materials for nuclear reactors due to the low neutron absorption cross-section, good corrosion resistance and acceptable mechanical properties. These properties are greatly dependent on microstructural and textural features, such as grain morphology, grain size, crystallographic texture and distribution of precipitates. It is necessary to understand microstructure and texture evolution during fabrication in order to optimize the manufacturing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Following hot-rolling experiments on zirconium alloy sheets, Chen Jianwei [22] observed that when there was an initial preference for the transverse direction in texture, the resulting texture after both hot and cold rolling resulted in a < 10 -10 >//RD basal texture. Luan, Xiao et al [23] conducted rolling experiments on annealed pure zirconium sheets, which initially exhibited a double-peak texture at room temperature. They observed that the texture remained largely consistent throughout the rolling process, with a gradual concentration along the ND direction.…”
Section: Introductionmentioning
confidence: 99%
“…Following hot-rolling experiments on zirconium alloy sheets, Chen Jianwei [22] observed that when there was an initial preference for the transverse direction in texture, the resulting texture after both hot and cold rolling resulted in a < 10 -10 >//RD basal texture. Luan, Xiao et al [23] conducted rolling experiments on annealed pure zirconium sheets, which initially exhibited a double-peak texture at room temperature. They observed that the texture remained largely consistent throughout the rolling process, with a gradual concentration along the ND direction.…”
Section: Introductionmentioning
confidence: 99%